CMCS-CuO NPs antibacterial latex and application of CMCS-CuO NPs antibacterial latex in clinical imbedded artificial pipeline base material
By blending CMCS-CuO NPs antibacterial materials with natural latex to prepare antibacterial latex, the problem of easily causing infection after being left in the human body is solved, and the effective antibacterial effect on common urinary tract pathogens is achieved, and good biosafety and histocompatibility are shown.
Patent Information
- Application Number
- CN202411855582.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-03-18
AI Technical Summary
Existing catheters or ureteral stent tubes are easily induce infection after being left in the human body. It is mainly due to the formation of biofilms on the surface. Traditional antibiotics are difficult to effectively kill bacteria and easily lead to bacterial resistance.
Antibacterial latex is prepared by blending CMCS-CuO NPs antibacterial materials with medical natural latex. Carboxymethyl chitosan composite nano-copper oxide (CMCS-CuO NPs) is generated by reaction under hydrothermal conditions, and blending it with natural latex to form antibacterial latex.
This antibacterial latex has a 100.0% antibacterial rate on bacteria such as Staphylococcus aureus, Staphylococcus epidermis, and the antibacterial rate on Enterococcus faecalis reaches 99.8%, effectively inhibiting bacterial growth, reducing biofilm formation, and reducing the incidence of urinary tract infection. At the same time, there is no obvious difference in cytotoxicity and good histocompatibility.
Smart Images

Figure CN119633180A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of medical material preparation, and particularly relates to a CMCS-CuO NPs antibacterial latex and application thereof in a clinically implantable artificial pipeline substrate. Background Art
[0002] Urology often uses various artificial tubes to be inserted into the human urethra to solve problems such as urinary system obstruction. The most common ones are urinary catheters and ureteral stents. These artificial tubes are placed in the human body according to clinical needs and can cause serious infections [1,2]. This infection is mainly caused by the change of the urethral microecological environment after long-term placement in the human body, and the formation of biofilms on the surface of these artificial tubes. The use of antibiotics is not only difficult to kill bacteria in the biofilm, but also prone to bacterial resistance, which increases the health burden of patients [3,4]. Nanometals, as an emerging class of antibacterial materials, not only have strong antibacterial ability, but also have a unique bactericidal mechanism compared with traditional antibiotics that can avoid bacterial resistance, and are increasingly attracting people's attention [5]. Nanocopper oxide (CuO nano-particles, CuO NPs) is one of the representatives of nanometals. It is low-priced, highly reactive, and can effectively inhibit the growth of viruses, bacteria, etc. [6]. Summary of the invention
[0003] In order to solve the problem that current catheters or ureteral stents and other tubes placed in the human body are prone to cause human infection, the present invention provides a CMCS-CuO NPs antibacterial latex and its application in a clinical implantable artificial conduit substrate.
[0004] The present invention is realized by the following technical scheme: a CMCS-CuO NPs antibacterial latex, carboxymethyl chitosan and copper sulfate are reacted under hydrothermal conditions to obtain a carboxymethyl chitosan composite nano copper oxide CMCS-CuO NPs antibacterial material, which is then blended with medical natural latex to prepare the CMCS-CuO NPs antibacterial latex.
[0005] The method for preparing the CMCS-CuO NPs antibacterial latex comprises the following specific steps: (1) Preparation of CMCS-CuO NPs antibacterial material: 5 mg / ml carboxymethyl chitosan CMCS aqueous solution and 10 mg / ml copper sulfate aqueous solution were prepared respectively. The CMCS aqueous solution was first slowly heated to 50°C, and then the copper sulfate aqueous solution was added dropwise to the CMCS aqueous solution at a volume ratio of 1:1. The mixture was stirred at a constant speed of 1000 rpm using a magnetic stirrer. The mixture was then heated to 100°C at a heating rate of 10°C / min. 2 mol / L sodium hydroxide solution was added dropwise to make the pH value of the mixed solution 10-11. The alkaline condition was maintained at 100°C for 5 min. The solution turned from light blue to black to obtain a CMCS-CuO NPs solution. The obtained solution was then dialyzed with deionized water in a 10 KD dialysis bag for 72 h to remove unabsorbed CMCS and excess impurity ions. The CMCS-CuO NPs antibacterial material was obtained by vacuum freeze drying at -60°C for 24 h. (2) Preparation of CMCS-CuO NPs antibacterial latex: Medical natural latex NRL was filtered three times using a 120-mesh sieve to remove solid impurities and then poured into a three-necked round-bottom flask. Nitrogen was introduced into the flask under sealed conditions while stirring at 300 rpm to remove ammonia in the emulsion. After the ammonia was completely removed, 1 mg of CMCS-CuO NPs material was dissolved in 2 ml of deionized water. After mixing evenly with a magnetic stirrer at 1000 rpm, 1 ml of NRL was mixed in by a blending method to obtain a uniformly dispersed liquid antibacterial latex.
[0006] The present invention also provides the use of the CMCS-CuO NPs antibacterial latex or the CMCS-CuO NPs antibacterial latex prepared by the method in a clinical implantable artificial conduit substrate.
[0007] Furthermore, the clinically implantable artificial conduit is a urinary catheter or a ureteral stent.
[0008] The present invention uses a simple and low-toxic method to reduce and stabilize CuO NPs with carboxymethyl chitosan (CMCS) to obtain an antibacterial material, and blends it with natural rubber latex (NRL), a base material for urinary catheters or ureteral stents commonly used in clinical practice, to obtain an antibacterial latex, and evaluates its in vitro antibacterial effect and biosafety against common pathogens of the urinary system. The results show that the antibacterial latex obtained by the present invention has an antibacterial rate of 100.0% for Staphylococcus aureus and Staphylococcus epidermidis, and an antibacterial rate of 99.8% for Enterococcus faecalis, indicating that this antibacterial latex can also well inhibit the growth of Gram-positive bacteria, thereby reducing the probability of surface biofilm formation and the incidence of urinary tract infection. Compared with the common latex catheters on the market, there is no obvious difference in cytotoxicity, and the tissue compatibility is good, which is expected to be applied to the field of medical materials, especially the preparation of artificial conduit catheters and ureteral stents in urology. BRIEF DESCRIPTION OF THE DRAWINGS
[0009] Figure 1 The CMCS-CuO NPs suspension is prepared by the method of the present invention; Figure 2 TEM results of CMCS- CuO NPs composites; Figure 3 The results of the MTT test showed that there was no significant difference in cytotoxicity between the antimicrobial latex and the latex catheter; Figure 4 The figure is a diagram of the tissue compatibility results of the antibacterial latex; in the figure: A is the antibacterial latex group G; B is the latex catheter group H; C is the control group I. DETAILED DESCRIPTION
[0010] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all the embodiments; based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0011] Unless defined otherwise, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention belongs, and the disclosure and materials cited therein are hereby incorporated by reference.
[0012] Technical equivalents to the specific embodiments described that are apparent to those skilled in the art using no more than routine experimentation are intended to be encompassed by this application.
[0013] The experimental methods in the following examples are all conventional methods unless otherwise specified. The instruments and equipment used in the following examples are all conventional laboratory instruments and equipment unless otherwise specified; the experimental materials used in the following examples are all purchased from conventional biochemical reagent stores unless otherwise specified.
[0014] 1. Experimental materials: CMCS (molecular weight 9000 Da, Shanghai McLean Biochemical Co., Ltd.), NRL (solid content about 61.5%, Shenzhen Hengyuan Chemical Plant), copper sulfate, sodium hydroxide (analytical grade, Tianjin Komiou Chemical Reagent Co., Ltd.), Escherichia coli, Proteus mirabilis, Klebsiella pneumoniae, Staphylococcus aureus, Enterococcus faecalis and Staphylococcus epidermidis (Laboratory of the Department of Laboratory, The First Hospital of Shanxi Medical University), MTT kit (Biyuntian Biotechnology Co., Ltd.), human bladder immortalized epithelial cells (SV-HUC-1, Cell Resource Center, Shanghai Institutes for Biological Sciences, Chinese Academy of Sciences), SD rats (SPF grade, male, 8-12 weeks old, Beijing Sibeifu Biotechnology Co., Ltd.), all reagents were prepared with deionized water.
[0015] 2. Experimental Methods 1. Preparation of CMCS-CuO NPs antibacterial material: 5 mg / ml CMCS solution and 10 mg / ml copper sulfate solution were prepared with deionized water, the CMCS solution was slowly heated to 50 °C, and then the copper sulfate solution was added to the CMCS solution at a volume ratio of 1:1. The mixture was stirred at a constant speed of 1000 rpm using a magnetic stirrer. After gradually heating to 100 °C at 10 °C / 5 min, 2 mol / L sodium hydroxide solution was added to make the pH of the mixed solution reach 10-11. The alkaline environment was kept at a constant temperature for 5 min. The solution completely changed from light blue to black to obtain a CMCS-CuO NPs solution. The mixed solution after the reaction was dialyzed with deionized water in a 10 KD dialysis bag for 72 h to remove excess ions and unadsorbed CMCS. The CMCS-CuO NPs composite material was obtained by vacuum freeze drying. The particle size and structure of the composite material were characterized by transmission electron microscope (TEM).
[0016] 2. Preparation of antibacterial latex: The blending method is simple and convenient, applicable to particles of various shapes, and is a common method for preparing nanocomposite materials [7]. The present invention adopts the blending method to prepare antibacterial latex. NRL is filtered through a 120-mesh sieve three times to remove solid impurities and then poured into a three-necked round-bottom flask. Under sealed conditions, nitrogen is introduced while stirring at a speed of 300 rpm to remove ammonia contained in the emulsion. After the ammonia is completely removed, 1 mg of CMCS-CuO NPs material is dissolved in 2 ml of deionized water, mixed evenly with a magnetic stirrer at 1000 rpm, and then mixed with 1 ml of NRL by blending to obtain a uniformly dispersed liquid antibacterial latex.
[0017] The obtained liquid antibacterial latex was dried in a fume hood at room temperature for 72 hours to obtain an antibacterial latex film as the experimental group A. A natural latex film prepared by the same method using NRL with only the same volume of deionized water added was used as the control group B.
[0018] 3. In vitro antibacterial property test of antibacterial latex: The main pathogens of the urinary system include Escherichia coli, Proteus mirabilis, Klebsiella pneumoniae, Staphylococcus aureus, Enterococcus faecalis and Staphylococcus epidermidis [8,9], and in vitro antibacterial tests were carried out specifically.
[0019] Each strain was inoculated onto nutrient agar medium (0.4% boric acid was added to the medium for Proteus mirabilis) by streaking method and cultured in a constant temperature incubator for 24 h. The colony was transferred to nutrient broth medium and cultured again for 24 h. After centrifugation and washing three times, it was diluted to a concentration of 10 with PBS buffer using a 0.5 McFarland turbidimetric standard gradient. 5 CFU / ml bacterial suspension for later use.
[0020] The colony count method was used to determine the colonies in each group
[10] . The films of groups A and B were cut into discs with a diameter of 10 mm, placed on the bottom of a 24-well plate, and evenly coated with 100 μL of the diluted bacterial suspension (10 5 CFU / ml) on the surface of the film, the blank control group C was a blank well of a 24-well plate with an equal amount of standard bacterial suspension added, and cultured at 37°C for 18-24h. The same volume of PBS buffer was used to fully shake and wash each group, and the washing solution was applied to the plate (boric acid was added to the culture medium of Proteus mirabilis) in triplicate, and the live colonies were counted after cultured at 37°C for 18-24h. The above experiment was repeated three times under the same conditions at different times, and the antibacterial rate was calculated using the following formula: Inhibition rate (%) = (number of colonies in the standard diluted bacterial solution - number of colonies in each group) / number of colonies in the standard diluted bacterial solution × 100.
[0021] 4. Cytotoxicity evaluation of antibacterial latex: Randomly cut the same mass of 1 cm latex sticks from antibacterial latex and common latex catheters on the market, add them into complete culture medium (Complete medium 7-1, CM7-1) (containing F-12k (90%), 10% fetal bovine serum, penicillin / streptomycin 100000u / L) at a ratio of 10 mg / ml, and incubate in 5% CO 2 The experimental group D was the antibacterial latex extract prepared by the present invention, the control group E was the common latex catheter extract on the market, and the control group F was cultured in ordinary complete culture medium. The culture medium of each group was prepared with a suspension of immortalized human bladder epithelial cells (cell concentration 4×10 7 / L) and placed in a 96-well plate in a 5% CO 2 The cells were cultured in a 37°C incubator, and each group was tested at 24h, 48h, 72h, and 96h according to the MTT kit steps. The absorbance at a wavelength of 570nm was detected by enzyme labeling.
[0022] 5. Tissue compatibility evaluation of antibacterial latex: SD male rats were randomly divided into three groups: the experimental group G was the antibacterial latex group prepared by the present invention, the control group H was the latex catheter group commonly found on the market, and the control group I was the sham operation group. After each group of rats was anesthetized with 3% isoflurane, the skin and abdominal muscle layer were cut about 2 cm above the pubic symphysis to expose the bladder, and a small incision was made on the outside of the bladder. Group I was directly sutured without implanting any material; Group G and Group H respectively cut the corresponding latex rods of about 1 cm of the same mass, and implanted them into the bladder after disinfection. After suturing layer by layer, the wound was disinfected and closely observed. After 14 days of overdose of anesthesia, the rats were killed, and the bladder tissue was immediately removed by opening the abdomen, fixed with paraformaldehyde, dehydrated routinely, and embedded in paraffin, and 5 μm thick tissue sections were cut for HE staining.
[0023] 3. Experimental Results and Discussion 1. Characterization of CMCS-CuO NPs: Under heating conditions, after adjusting the pH, CMCS reduces copper sulfate to stably generate CuO and adsorbs on its surface to prevent the nanoparticles from agglomerating into blocks. The mixed solution changes from light blue transparent to black, and there is no agglomeration or precipitation in the solution, indicating that the CMCS-CuO NPs prepared by this method have high stability. Normal CuO is insoluble in water. The CMCS in the CMCS-CuO NPs prepared by this method increases the water solubility of CuO, such as Figure 1 A relatively uniform suspension can be obtained as shown. After freeze drying, a black powder was obtained. The morphology and distribution of CMCS-CuO NPs were tested by TEM. The results are shown in Figure 2As shown, the prepared CuO NPs have good dispersion in the CMCS matrix, the particle diameters are similar and most of them are spherical or nearly spherical, and the size distribution is concentrated in 5-10nm.
[0024] The size, shape and other characteristics of nanometallic materials have an impact on their antibacterial effectiveness. Small-sized nanometallic materials generally have stronger antibacterial properties
[11] . The CuO NPs prepared in the present invention not only have low raw material prices, simple processes, and no introduction of toxic compounds, but also have a smaller size (usually 10-50nm) compared with other studies [12,13], and may have stronger antibacterial properties.
[0025] 2. In vitro antibacterial properties of antibacterial latex: The antibacterial rates of different groups compared with standard diluted bacterial solution are shown in Table 1. The results show that the antibacterial latex has strong antibacterial activity against Escherichia coli, Proteus mirabilis, Klebsiella pneumoniae, Staphylococcus aureus, Enterococcus faecalis and Staphylococcus epidermidis. Compared with the control group C, the antibacterial latex group A showed a broad and obvious contact antibacterial effect. Since natural latex is rich in nutrients such as protein
[14] , it has a proliferative effect on bacterial growth, so group B showed an effect that was conducive to bacterial growth, and the antibacterial rates were all negative.
[0026] Table 1. Antibacterial rate of different groups compared with standard dilution solution Escherichia coli is one of the most common pathogens causing urinary tract infections. It can mutate to produce drug-resistant genes and spread through plasmids. The widespread use and abuse of antibiotics has also accelerated the increase in drug resistance, and the formation of biofilms has exacerbated the transmission of such drug-resistant genes
[15] . The CMCS-CuO NPs in the antibacterial latex prepared by the present invention have extremely strong bactericidal ability, and it is difficult for Escherichia coli to grow on its surface, and it is even more difficult to form a biofilm. This may be because CuO NPs can destroy the bacterial cell structure, produce oxidative stress and damage bacterial DNA, ultimately leading to the death of Escherichia coli
[16] . In addition, common Gram-negative bacteria in urinary tract infections also include Klebsiella pneumoniae and Proteus mirabilis. The antibacterial rates of Group A antibacterial latex against them are 99.7% and 99.3%, respectively, indicating that the antibacterial latex prepared by the present invention has a broad-spectrum bactericidal ability against Gram-negative bacteria. As for Gram-positive bacteria, the results showed that the antibacterial rate of Group A antibacterial latex against Staphylococcus aureus and Staphylococcus epidermidis was 100.0%, and the antibacterial rate against Enterococcus faecalis was 99.8%, indicating that this antibacterial latex can also effectively inhibit the growth of Gram-positive bacteria, thereby reducing the probability of surface biofilm formation and reducing the incidence of urinary tract infections.
[0027] 3. Cytotoxicity of antibacterial latex: MTT experiment can understand the effect of antibacterial latex on cell growth and survival, which is of great significance for evaluating the cytotoxicity of antibacterial latex to the human urinary tract. The present invention selects the representative of urothelial cells - human bladder immortalized epithelial cells for detection, and the results are as follows Figure 3 As shown in the figure, the results showed that each group was cultured for 96 hours, and the OD value of each well of each group was detected at each time point (the increase in OD value represents the cell proliferation amplitude). Among them, the immortalized human bladder epithelial cells of group F in the control group grew and proliferated well over time, while the cell proliferation of groups D and E was slower than that of the ordinary culture medium, but there was no obvious difference between the two, indicating that the antibacterial latex prepared by the present invention has no obvious cytotoxicity difference compared with the common latex catheters on the market.
[0028] 4. Tissue compatibility of antimicrobial latex: Tissue embedding or in vivo placement followed by pathological observation is usually used for tissue compatibility evaluation [17,18]. The present invention implanted antimicrobial latex into the bladder of rats to simulate the common retention time of 14 days for artificial urinary catheters and ureteral stents in the clinical urinary system, and observed and compared the pathological damage. The results are as follows Figure 4 As shown, the results show that after 14 days of indwelling, each group has a certain degree of bladder mucosal thickening and inflammatory reaction, which may be related to surgery and foreign body friction. The control group I group has the lightest degree, and there is no significant difference in the degree of injury in the antibacterial latex group G group and the latex catheter group H group. It shows that the antibacterial latex prepared by the present invention has good tissue compatibility. HE staining shows that each group has a certain degree of mucosal thickening and inflammatory reaction, but there is no significant difference between the G group and the H group.
[0029] With the advancement of medicine, medical devices used for auxiliary treatment, such as catheters and ureteral stents, have been widely used in urology. Infection is one of the most serious complications associated with such artificial conduit placement surgeries. Bacteria can not only float, but also colonize on the surface of artificial conduits and form biofilms, increasing bacterial antibiotic resistance, making infections difficult to treat and bringing heavy pressure. CMCS is an excellent material with certain broad-spectrum antibacterial ability and reduction stability
[19] . CMCS can help generate CuO NPs and stabilize them, increase water solubility, and the combination of the two can improve antibacterial performance. The raw materials of the present invention are widely available, and the preparation process is simple and green. The prepared CMCS-CuO NPs composite antibacterial material has good water solubility and can be mixed with different liquid materials as needed. It is blended with NRL, which has good biocompatibility and physical properties, to form an antibacterial latex, which has homogeneous antibacterial agents from the inside out, while avoiding problems such as decreased antibacterial ability caused by coating shedding. The results of in vitro antibacterial experiments show that the antibacterial latex has the ability to contact inhibit the six most common bacteria that cause urinary tract infections, thereby effectively preventing bacteria from adhering to form biofilms. At the same time, CMCS-Cu0 NPs-NRL has good formability, and its physical properties can be changed as needed in the future. Compared with the common latex catheters mentioned above, the antibacterial latex has no obvious differences in cytotoxicity and tissue compatibility, and has high biosafety. Through further research and evaluation in the future, it is expected to be used in the field of medical materials, especially in the preparation of artificial conduit catheters and ureteral stents in urology.
[0030] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
[0031] References: 1. Zhang Wei, Zhang Juanjuan, Ren Yanli, Wang Weiwei, Shang Anquan. Analysis of pathogen distribution and risk factors of catheter-related urinary tract infection[J]. Chinese Journal of Disinfection. 2019;36(07):532-534. 2. Kozyrakis D, Perikleous S, Chatzistamou SE, et al. Is There a Role for Double J Stent Culture in Contemporary Urology? Urologia internationalis. 2018;100(2):203-208. 3. Jamal M, Ahmad W, Andleeb S, et al. Bacterial biofilm and associated infections. Journal of the Chinese Medical Association: JCMA. Jan 2018;81(1):7-11. 4. Scotland KB, Lo J, Grgic T, Lange D. Ureteral stent-associatedinfection and sepsis: pathogenesis and prevention: a review. Biofouling. Jan 2019;35(1):117-127. 5. Zheng Y, Wei M, Wu H, Li F, Ling D. Antibacterial metalnanoclusters. J Nanobiotechnology. 2022 Jul 16;20(1):328. 6. Wang Xinyu. Preparation of Nano-copper Oxide and Study on Its Antibacterial Properties[D]. Shenyang University of Technology, 2023. 7. Kang Chenghu. Preparation and performance progress of polymer-based nano-inorganic composites[J]. Plastics, 2023, 52(04): 172-177. 8. McLellan LK, Hunstad DA. Urinary Tract Infection: Pathogenesis andOutlook. Trends in molecular medicine. Nov 2016;22(11):946-957. 9. Tang J. Microbiome in the urinary system—a review. AIMS Microbiology. 2017;3(2):143-154. 10. Wang H, Gong X, Miao Y, et al. Preparation and characterization of multilayer films composed of chitosan, sodium alginate and carboxymethylchitosan-ZnO nanoparticles. Food Chemistry.2019;283:397-403. 11. Zuo Jiasheng, Qin Ying, Zhao Zuzhen, et al. Research progress on preparation, properties and antibacterial application of medical nanometals and their oxides[J]. Chinese Journal of Biotechnology, 2023, 39(04): 1462-1476. 12. Liu Hui, Wang Shuzhong, Yang Jianqiao, et al. Preparation of Nano-copper and Copper Oxide by Supercritical Hydrothermal Method from Acidic Etching Waste Liquid [J / OL]. Journal of Shanghai Jiaotong University, 1-21 [2024-10-29]. 13. Zheng Kaiyi, Wei Chuangchuang, Wang Yuhao, et al. Green synthesis of nano copper oxide particles and study on their in vitro anti-PRRSV effect[J]. Heilongjiang Animal Husbandry and Veterinary Medicine, 2023, (18): 109-114. 14. Marques PAC, Guerra NB, Dos Santos LS, et al. Natural rubberlatex-based biomaterials for drug delivery and regenerative medicine: Trends and directions. Int J Biol Macromol. 2024;267(Pt 2):131666. 15. Öztürk FY, Darcan C, Kariptaş E. The Determination, Monitoring, Molecular Mechanisms and Formation of Biofilm in E. coli. Braz J Microbiol. 2023;54(1):259-277. 16. Guan G, Zhang L, Zhu J, Wu H, Li W, Sun Q. Antibacterialproperties and mechanism of biopolymer-based films functionalized by CuO / ZnOnanoparticles against Escherichia coli and Staphylococcus aureus. J HazardMater. 2021;402:123542. 17. Lai Xinning, Xiao Bo, Huang Yuguang, et al. Formation of local anesthetic sustained-release coating on the surface of urinary catheter and its analgesic effect[J]. Chinese Journal of Biomedical Engineering, 2021, 40(06): 712-718. 18. Tang Mengmeng, Chen Hechun, Xie Hongchen, et al. Histocompatibility of poly (L-lactide-ε-caprolactone) / cross-linked polyvinyl pyrrolidone ureteral stent implanted in rat bladder[J]. Chinese Journal of Tissue Engineering Research, 2020, 24(04): 583-588. 19. Shariatinia Z. Carboxymethyl chitosan: Properties and biomedical applications. Int J Biol Macromol. 2018;120(Pt B):1406-1419.
Claims
1. A CMCS-CuO NPs antibacterial latex, characterized in that: Carboxymethyl chitosan and copper sulfate were reacted under hydrothermal conditions to obtain carboxymethyl chitosan composite nano copper oxide CMCS-CuO NPs antibacterial material, which was then blended with medical natural latex to prepare CMCS-CuO NPs antibacterial latex.
2. A method for preparing the CMCS-CuO NPs antibacterial latex according to claim 1, characterized in that: The specific steps are as follows: (1) Preparation of CMCS-CuO NPs antibacterial material: 5 mg / ml carboxymethyl chitosan CMCS aqueous solution and 10 mg / ml copper sulfate aqueous solution were prepared respectively. The CMCS aqueous solution was first slowly heated to 50°C, and then the copper sulfate aqueous solution was added dropwise to the CMCS aqueous solution at a volume ratio of 1:
1. The solution was stirred at a constant speed of 1000 rpm with a magnetic stirrer, and then heated to 100°C at a heating rate of 10°C / min. 2 mol / L sodium hydroxide solution was added dropwise to make the pH value of the mixed solution 10-11. The alkaline condition was maintained at 100°C for 5 min. The solution changed from light blue to black to obtain CMCS-CuO NPs solution. The obtained solution was then dialyzed with deionized water in a 10KD dialysis bag for 72 h to remove unabsorbed CMCS and excess impurity ions. The CMCS-CuO NPs antibacterial material was obtained by vacuum freeze drying at -60°C for 24 h. (2) Preparation of CMCS-CuO NPs antibacterial latex: Medical natural latex NRL was filtered three times using a 120-mesh sieve to remove solid impurities and then poured into a three-necked round-bottom flask. Nitrogen was introduced into the flask under sealed conditions while stirring at 300 rpm to remove ammonia in the emulsion. After the ammonia was completely removed, 1 mg of CMCS-CuO NPs material was dissolved in 2 ml of deionized water. After mixing evenly with a magnetic stirrer at 1000 rpm, 1 ml of NRL was mixed in by a blending method to obtain a uniformly dispersed liquid antibacterial latex.
3. Use of the CMCS-CuO NPs antibacterial latex according to claim 1 or the CMCS-CuO NPs antibacterial latex prepared by the method according to claim 2 in a clinical implantable artificial conduit substrate.
4. The use according to claim 3, characterized in that: The clinically inserted artificial conduit is a urinary catheter or a ureteral stent.
Citation Information
Patent Citations
Preparation method of compound bactericide
CN118020792A
Preparation fastening wound healing
RU2460532C1